(3GdhTGM hJKbja GdQeGM aj QO Jhgje GdeLO GdUMGMs - (3CHh RjO YHO GdQMef Hf YHO GdYRjR GdeZQHj GdJGOdj GdeOfj GdYeQjs
(3ChdgG (B:s
(3GdMeO ddg GdaJGM GdhgGH , GdgGOi ef TGA ef YHGOg Edi UhH GdUhGH EYde Cf Yde GddZI ef CTQa GdYdhe bOQkG hCMdGgG ePGcQI s
(3BNQgG (B:s
(3bdJ (B: (3hefg CjVkG (B: (3HbjJ HbGA GdOgQ jG cga Cgdg hgPG OYGA ddHQjI TGed hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1279s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO Hf Ydi GdeLGgO GdNGUI HJYR s
Keywords: (3GddZIs